2022
DOI: 10.1002/ece3.8560
|View full text |Cite
|
Sign up to set email alerts
|

RAD‐tag and mitochondrial DNA sequencing reveal the genetic structure of a widespread and regionally imperiled freshwater mussel, Obovaria olivaria (Bivalvia: Unionidae)

Abstract: Obovaria olivaria is a species of freshwater mussel native to the Mississippi River and Laurentian Great Lakes‐St. Lawrence River drainages of North America. This mussel has experienced population declines across large parts of its distribution and is imperiled in many jurisdictions. Obovaria olivaria uses the similarly imperiled Acipenser fulvescens (Lake Sturgeon) as a host for its glochidia. We employed mitochondrial DNA sequencing and restriction site‐associated DNA sequencing (RAD‐seq) to assess patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…This is likely due to freshwater connectivity within the Mississippi basin and, we speculate, a post-glacial radiation into the Lake Erie basin. In contrast, other studies have found more population differentiation among freshwater mussels from the Mississippi basin and the Great Lakes; namely Obovaria olivaria ( Bucholz et al, 2022 ), Elliptio dilatata and Actinonaias ligamentina ( Elderkin et al, 2008 ), Amblema plicata ( Elderkin et al, 2007 ), and Cumberlandia monodonta ( Inoue et al, 2014 ). However, some key differences in these species compared to P. pustulosa include smaller ranges or sampling sites that do not extend into Texas, and much lower haplotype diversity, which limit direct comparisons.…”
Section: Discussionmentioning
confidence: 70%
“…This is likely due to freshwater connectivity within the Mississippi basin and, we speculate, a post-glacial radiation into the Lake Erie basin. In contrast, other studies have found more population differentiation among freshwater mussels from the Mississippi basin and the Great Lakes; namely Obovaria olivaria ( Bucholz et al, 2022 ), Elliptio dilatata and Actinonaias ligamentina ( Elderkin et al, 2008 ), Amblema plicata ( Elderkin et al, 2007 ), and Cumberlandia monodonta ( Inoue et al, 2014 ). However, some key differences in these species compared to P. pustulosa include smaller ranges or sampling sites that do not extend into Texas, and much lower haplotype diversity, which limit direct comparisons.…”
Section: Discussionmentioning
confidence: 70%
“…However, this biogeographic pattern contrasts with unionid mussels in the tribes Rectidentini and Contradentini (e.g., Hyriosis 4 , 6 , Ensidens 4 , 8 , Physunio 4 , and Lens 4 ), in which the Lower Mekong lineages are relatively close to those of the Chao Phraya Basin. These contradictory biogeographic patterns may reflect the difference in historical radiation in Indochina River systems among different unionid tribes, and thus inviting further comparative biogeographic studies of multiple unionid taxa with extensive sampling throughout the distribution range and modern genomic techniques (e.g., RADseq derived SNPs 64 , 65 ) to be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize genetic diversity, we performed reduced‐representation genomic sequencing (Ali et al, 2016; Andrews et al, 2016) following the Best‐RAD protocol (Ali et al, 2016; Bucholz et al, 2022). DNA was normalized to 10 ng/μL/individual.…”
Section: Methodsmentioning
confidence: 99%